ASSESSMENT OF ENVIRONMENTAL CONDITIONS IN TASHKENT AND RELATIONSHIP WITH THE POPULATION SUFFERING FROM CARDIOVASCULAR DISEASES (American Journal of Interdisciplinary Research and Development, 2024)
To study the health status of the population suffering from cardiovascular diseases, taking into account the degree of atmospheric air pollution with nitrogen compounds, to develop preventive measures (on the example of Tashkent). To achieve this goal, 4 interrelated tasks were solved. During the scientific research, the atmospheric air and the health of the population of the city of Tashkent were chosen as the object. The subject of the study was the levels of atmospheric air pollution with nitrogen compounds and cardiovascular diseases of the population (on the example of Tashkent).